Efeito protetor do exercício físico nas alterações bioquímicas e cognitivas iniciais e tardias induzidas pelo traumatismo cranioencefálico em ratos - Fiorin, Fernando da Silva (2014)
Traumatic brain injury (TBI) is a major cause of morbidity and mortality in industrialized countries leading to the motor and cognitive deficits. Evidence demonstrated that exercise is neuroprotective in traumatic brain injury. However, the effects of exercise before of the TBI at the cognitive function are unknown. Role of excitotoxicity and oxidative damage in secondary damage of TBI, however, until this moment, were not demonstrated if exists a relationship between early phase of damage and the late cognitive deficit. In the current study, we proposed that improvement cognitive response induced by exercise prior in rats after a TBI can be associated with the neuroprotection of early phase after injury. To demonstrate this hypotheses, adult rats practice swimming exercise during 6 weeks followed for TBI operation. We assessed the motor alterations of early phase, the glutamate uptake and antioxidant defense in twenty four hours (24 h) and 15 days after TBI. Acquisition of memory was assessed by recognition object task on days 15 post TBI. Moreover, we evaluated the brain-derived neurotrophic factor (BDNF) to assessement the synaptic plastic. In the present study, we showed that TBI induced by fluid percussion injury (FPI) in adult male Wistar rats induced early motor impairment 24 h, followed by learning retention deficit (2 weeks after neuronal injury). Previous swimming training improved the memory in object recognition task per se and protected against FPI-related disabilities. Although the FPI did not alter hippocampal expression of glutamate transporters (EAAT1 / EAAT2) and brain-derived neurotrophic factor (BDNF), the alterations in the redox status, herein characterized by DCFH-DA oxidation and SOD activity inhibition, led to marked impairment of protein functionally (Na+, K+-ATPase activity inhibition) and glutamate uptake inhibition 24 h after neuronal injury in sedentary injured rats. Indeed, the early increase of nuclear factor erythroid 2-related factor (pNRF2/NRF2 ratio) followed by a repair mechanism (protein HSP70 expression), 24 h and 2 weeks after neuronal injury, suggests that FPI-induced signal transduction may exert compensatory effect on pathophysiological processes. In this report we showed that previous physical exercise induced the increase of immune content of glutamate transporters (EAAT1/ EAAT2), pNrf2/Nrf2 ratio, SOD enzyme and HSP70 per se besides preventing against FPI-induced Na+, K+ - ATPase activity, glutamate uptake inhibition DCFH-DA oxidation 24 h after neuronal injury. The enhancement of hippocampal pNrf2/Nrf2 and HSP70 immune content in trained injured when compared with sedentary rats suggest that protein expression modulation associated to antioxidant defense elicited by previous physical exercise prevent against toxicity induced by TBI. The significant increase of BDNF levels in trained injured rats 24 h and 2 weeks strongly reinforce the idea that physical activity alters neuronal functions and thus delays or prevents secondary cascades that leave the neurobehavioral disability after TBI.